Influence of Water Injection on Performance and Emissions of A Direct Injection Jet Ignition Engine - Boretti, Albert; Scalzo, Joseph (Journal of Environmental Science and Engineering Technology, 2015)
A computational model is used to describe the operation of a four cylinder, turbocharged, ignition controlled by spark, direct injection engine fuelled with different fuels, including hydrocarbons, oxygenates and hydrogen. The intercooled engine features port and direct water injection plus jet ignition. The direct water injection permits a further enhanced control of the conditions within the cylinder prior, during and after combustion. Thanks to water injection, a much higher compression ratio is adopted. The port injection of water drastically reduces the temperature of the inlet air, thus permitting more air to enter the cylinder. This translates in more fuel being introduced, for an increased torque and power output. The lower temperature of the air coupled to the direct injection during the compression stroke also improves the resistance to knock, and reduces the heat loss at the walls of the combustion chamber, further improving the fuel conversion efficiency that is already boosted by the use of an higher compression ratio. The enhanced control of the injection of water in the port and the direct injection of fuel in the cylinder is aimed to achieve near to knocking conditions in a stoichiometric mixture about top dead centre that is then ignited almost instantaneously by the jet ignition device. This permits very high fuel conversion efficiencies and high power density during the full load operation. The direct water injection further improves the in-cylinder conditions especially after combustion. Further investigations are needed to better optimise the port and direct water injections.